SERVANT LEADERSHIP AS POLITICAL WILL TO PERFORM A NON-PROFIT ORGANIZATION IN THE CITY OF TANGERANG SELATAN - Hasanah Hasanah; Dwi Oktariani; Nur Asni Gani; Andry Priharta (JWP (Jurnal Wacana Politik), 2023)
An organization is a place for several people or groups who carry out activities calling for goals with profit and non-profit plans. Organizational development, both profit and non-profit, requires a leader who can show his political will to run the organization. A leader in a non-profit organization still needs to pay attention to the interests of the members and those served. This study discusses servant leadership as political will in running non-profit organizations in South Tangerang City, Banten, Indonesia. The method used is qualitative, with a case study in a non-profit organization in the South Tangerang area. The study involved four informants with focus group discussions. Each informant stated the questions submitted. This study looks at five categories of servant leadership or servant leadership as the political will to run non-profit organizations, through the categories of servant leadership namely (1) delegation, (2) integrity, (3) motivation, (4) human resource development, (5) Remembering to communicate, that leaders in non-profit organizations in South Tangerang City are politically aware that servant leadership is a form of self-will in running an organization. Leaders in non-profit organizations are passionate about developing teams and meeting members’ needs in a disinterested organization, not for the personal needs of a leader.